Insights into the regulation of hearing regeneration - Khalaily, Lama; Avraham, Karen B. (Frontiers in Audiology and Otology, 2024)
Our perception of sound is mediated by sound-sensitive hair cells in the inner ear, located in a specialized neuro-epithelium that transmits information to the auditory cortex via the auditory pathway. A major cause of hearing loss is damage to and the death of these sensory hair cells. In humans, hair cells are only generated during embryonic development and cannot be replaced if damaged due to aging, excessive noise, ototoxic drugs, or illness. Much research is currently being invested worldwide in identifying methods to improve the ability to regenerate hair cells and circumvent their age-dependent limitations. Compared to numerous studies focused on gene therapy to restore deafness caused by a specific mutation before the onset of hair cell damage, research on auditory epigenetics is relatively recent. Although research indicates that epigenetic alterations play a crucial role in the differentiation, development, and regeneration of auditory hair cells, a dearth of comprehensive knowledge still exists regarding the specific role played by epigenetic modifications in the auditory system, with a particular emphasis on their potential correlation with the function and development of the auditory system. In addition, these modifications have been linked to the regeneration of hair cells caused by using pharmaceutical inhibitors (e.g., inhibition of the Notch pathway) and genetic (e.g., induced Atoh1 expression) treatments, which can lead to regenerating hair cells and restoring hearing. Recent developments in targetable epigenome-editing tools, such as CRISPR, and direct reprogramming enable targeted genome editing. In addition, the emergence of organoids and epigenetic drugs presents novel prospects for hearing restoration by manipulating regeneration pathways, making them promising methods for future regenerative treatments for hair cells. The potential of epigenetic modifiers as viable targets for pharmacological manipulation is becoming evident. Future therapies aimed at hair cell regeneration are particularly beneficial because of their advantage of restricting drug exposure within the inner ear.